Agricultural R&D: investing in Africa’s future analyzing trends, challenges, and opportunities: reflection on the conference - Lynam, John; Beintema, Nienke M.; Annor-Frempong, Irene (International Food Policy Research Institute, 2012)
The goal of the conference was to define a road map for revitalizing agricultural research in the region focusing on four principal themes: -sustainable financing of agricultural research; -training the next generation of agricultural scientists; -effectively evaluating the performance of research institutes and systems; and -efficient organization of national agricultural research activities supported by regional and international capacities. This document synthesizes the paper presentations, panel discussions and deliberations by the conference participants.The commissioned conference papers have been published as an ASTI/IFPRI–FARA Working Paper series, and a book synthesizing both the conference outcomes and further analysis will be prepared for publication in 2013.